Integrating Lean Warehousing and Systematic Analysis to Minimize Waste in Finished Product Storage: A Case Study and Generalizable Improvement Framework - Qurtubi; Haswika; Hari Purnomo; Pham Trung Kien (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Efficient warehouse management is critical for make-to-order production systems. This study investigates waste reduction in a metal casting company’s finished-product warehouse by applying Lean Warehousing principles. Using time-motion studies, Value Stream Mapping (VSM), Pareto diagrams, and fishbone diagrams, the research analyzed 13 workstations and identified five primary areas of waste. Simulation results demonstrated a significant cycle time reduction from 2,559 to 2,128 seconds, alongside an increased proportion of value-added activities. Although limited to a simulation, the findings highlight the effectiveness of Lean tools in standardizing work and redesigning layouts. The study concludes that continuous monitoring and Lean implementation are essential for achieving sustainable operational efficiency and reducing costs in industrial warehousing.